Pemanfaatan Kartu Gambar untuk Memahami Majas dalam Pembelajaran Puisi pada Siswa XI SMA Negeri 1 Kefamenanu - Yanuaria Hoar; Giri Indra Kharisma; Vincentius Mauk (Nexus Publishing, 2025)
This study aims to describe the use of picture cards as a learning medium to enhance students’ understanding of figurative language (majas) in poetry learning among eleventh-grade students at SMA Negeri 1 Kefamenanu. The background of this research stems from students' limited comprehension of stylistic elements in poetry, which negatively affects their interest and ability in writing poems. To address this issue, innovative teaching media such as picture cards are required. This research employed a qualitative descriptive approach with data collected through questionnaires and tests, both individual and group-based. The participants consisted of 21 eleventh-grade students. The findings reveal that the use of picture cards contributes positively to students' understanding and application of various types of figurative language, such as metaphor, personification, hyperbole, simile, and others. The results from individual assignments indicate that most students achieved scores above the minimum completeness criteria, while group activities also demonstrated a strong grasp of the material. Furthermore, student responses to the use of picture cards were highly positive, as reflected in the questionnaire scores, which suggest that the medium effectively supports students in understanding and writing poetry that includes figurative language. In conclusion, picture cards are proven to be an effective instructional medium that enhances conceptual understanding of figurative language, while also fostering students’ interest and active participation in poetry learning. It is recommended that Indonesian language teachers creatively utilize this medium to improve learning outcomes, particularly in the teaching of poetry.